Effect of Process Parameters on Corrosion Resistance of Ni-P-Al2O3 Composite Coatings Using Electrochemical Impedance Spectroscopy - Gadhari,Prasanna (2015)
Electroless nickel composite coatings are developed by incorporating soft/hard particles into Ni-P coatings, to improve mechanical as well as tribological properties. The objective of the present work is to investigate the effect of various coating process parameters on the corrosion behavior of Ni-P-Al2O3 composite coating deposited on mild steel substrate. The electrochemical impedance spectroscopy test is used to evaluate the corrosion behavior of the heat treated composite coatings at various annealing temperatures (300 °C, 400 °C, and 500 °C). Corrosion properties, charge transfer resistance (Rct) and double layer capacitance (Cdl), are optimized using Taguchi based grey relational analysis to improve the corrosion resistance of the coating. Concentration of nickel source, concentration of reducing agent, concentration of alumina particles and annealing temperature, are considered as a main design factor for optimization of electrochemical properties. Analysis of variance (ANOVA) is used to find out the optimum combination of coating process parameters. From ANOVA result, it is found that the concentration of Al2O3 particles and annealing temperature have significant influence on the corrosion resistance of the composite coatings. Concentration of reducing agent has moderate influence on the corrosion resistance. Surface morphology of the coated surface is studied using SEM (scanning electron microscopy) and chemical composition of the coating is studied using EDX (energy dispersive X-ray analysis). The XRD (X-ray diffraction analysis) is used to understand the phase transformation behavior of the composite coatings.